Estimation of CO2 Emissions from Transportation, Waste, and Energy Activities in Office Environments - Fidela Almadea; Raden Kokoh Haryo Putro (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Office activities contribute to carbon dioxide (CO2) emissions through transportation, electricity consumption, waste generation, and LPG use. This study estimates CO2 emissions from a municipal government office in Kediri City using the IPCC Tier 2 methodology. Data were collected through vehicle counts, electricity consumption records, waste measurements, and interviews regarding LPG usage. The results show that electricity consumption is the dominant source of emissions, accounting for 51,120 kg CO2/year. Transportation activities contributed 882 kg CO2/year, while waste generation and LPG consumption generated 133.28 kg CO2/year and 161.17 kg CO2/year, respectively. Overall, energy use is the primary driver of emissions in office environments. These findings provide baseline data to support energy efficiency improvements and sustainable office management strategies to reduce carbon emissions .Contribution to Sustainable Development Goals (SDGs)SDG 13 – Climate ActionSDG 7 – Affordable and Clean EnergySDG 11 – Sustainable Cities and CommunitiesSDG 12 – Responsible Consumption and Production